2009
DOI: 10.1071/fp08330
|View full text |Cite
|
Sign up to set email alerts
|

Estimating nitrogen uptake of individual roots in container- and field-grown plants using a 15N-depletion approach

Abstract: We only have a limited understanding of the nutrient uptake physiology of individual roots as they age. Despite this shortcoming, the importance of nutrient uptake processes to our understanding of plant nutrition and nutrient cycling cannot be underestimated. In this study, we used a 15 N depletion method that allowed for the measurement of nitrate-N uptake rates on intact, individual, fine roots of known age. We expected that N uptake would decline rapidly as fine roots aged, regardless of the environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 61 publications
2
12
0
Order By: Relevance
“…2 Relationships between tissue N concentration (N root , mg g −1 ) and the respiration rate per unit dry mass (F root , nmol CO 2 g −1 s −1 ) of the fine root segments from Tilia amurensis and Pinus koraiensis at the Xiaoxing'an Mountain, Northeastern China. The total number of fine root samples we measured was 46 for Tilia amurensis and 44 for Pinus koraiensis, respecrively who found that most sugar maple roots <0.5 mm in surface soil respired much higher than those of roots in larger diameter class, and demonstrated that there was a large variability within diameter class of the fine roots as previously studied (Wells and Eissenstat 2001;Pregitzer 2002;Volder et al 2009). Our root respiration results were characterized by a wide range of variability, some of which was likely associated with the sampling strategies.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…2 Relationships between tissue N concentration (N root , mg g −1 ) and the respiration rate per unit dry mass (F root , nmol CO 2 g −1 s −1 ) of the fine root segments from Tilia amurensis and Pinus koraiensis at the Xiaoxing'an Mountain, Northeastern China. The total number of fine root samples we measured was 46 for Tilia amurensis and 44 for Pinus koraiensis, respecrively who found that most sugar maple roots <0.5 mm in surface soil respired much higher than those of roots in larger diameter class, and demonstrated that there was a large variability within diameter class of the fine roots as previously studied (Wells and Eissenstat 2001;Pregitzer 2002;Volder et al 2009). Our root respiration results were characterized by a wide range of variability, some of which was likely associated with the sampling strategies.…”
Section: Discussionmentioning
confidence: 91%
“…While in other studies, fine roots were defined as <2 mm Pregitzer 1992, 1993;Gordon and Jackson 2000) or <1 mm in diameter class (Thomas et al 1999;Majdi et al 2008). Recent studies have demonstrated that fine roots are composed of individual roots that differ greatly in physiological functions and morphological characteristics rather than physiologically identical units (Eissenstat and Achor 1999;Eissenstat et al 2000;Pregitzer 2002;Volder et al 2009). Furthermore, individual roots within the broadly defined classes can differ greatly in respiration, nutrient uptake Majdi et al 2001;Ruess et al 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Root observations were made with root-access boxes (rhizotrons) with a clear transparent window that allows a root to be followed from birth and then sampled at a known age (Comas et al, 2000;Bouma et al, 2001;Resendes et al, 2008;Volder et al, 2009). Root boxes (0.6 · 0.5 · 0.4 m deep) were installed in a pit dug to the size of the box in April 2008, with the transparent window facing the tree, c. 1 m from the trunk and with all but the top 5 cm below the soil surface ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Roots also change with age in a number of physiological parameters, including respiration, nutrient uptake kinetics and phenolic compounds. Nitrate uptake, for example, is very high when the root is first born, but declines markedly after just a few days (Volder et al. 2005, 2009).…”
Section: Ageing Effects On Grape Root Functionmentioning
confidence: 99%